What does the effectiveness of management depend on ? - Ilyosbek Khasanov (Academia Open, 2019)
This paper makes analyses on improving the effectiveness of the agricultural management system will depend primarily on management functions. Management of these functions relies on the liberalization of the economy. Improvement of economic methods depends on economic, administrative and social-psychological research